Dietary Inflammatory Index and Non-Communicable Disease Risk: A Narrative Review - Phillips, Catherine M.; Chen, Ling-Wei; Heude, Barbara; Bernard, Jonathan Y.; Harvey, Nicholas C.; Duijts, Liesbeth; Mensink-Bout, Sara M.; Polanska, Kinga; Mancano, Giulia; Suderman, Matthew; Shivappa, Nitin; Hébert, James R. (Nutrients, 2019)
There are over 1,000,000 publications on diet and health and over 480,000 references on inflammation in the National Library of Medicine database. In addition, there have now been over 30,000 peer-reviewed articles published on the relationship between diet, inflammation, and health outcomes. Based on this voluminous literature, it is now recognized that low-grade, chronic systemic inflammation is associated with most non-communicable diseases (NCDs), including diabetes, obesity, cardiovascular disease, cancers, respiratory and musculoskeletal disorders, as well as impaired neurodevelopment and adverse mental health outcomes. Dietary components modulate inflammatory status. In recent years, the Dietary Inflammatory Index (DII®), a literature-derived dietary index, was developed to characterize the inflammatory potential of habitual diet. Subsequently, a large and rapidly growing body of research investigating associations between dietary inflammatory potential, determined by the DII, and risk of a wide range of NCDs has emerged. In this narrative review, we examine the current state of the science regarding relationships between the DII and cancer, cardiometabolic, respiratory and musculoskeletal diseases, neurodevelopment, and adverse mental health outcomes. We synthesize the findings from recent studies, discuss potential underlying mechanisms, and look to the future regarding novel applications of the adult and children’s DII (C-DII) scores and new avenues of investigation in this field of nutritional research.